2020
DOI: 10.3389/fpsyg.2020.547627
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Competence, Entrepreneurial Self-Efficacy, and Entrepreneurial Intention: A Study Based on China College Students’ Social Entrepreneurship Project

Abstract: Entrepreneurship education has a lot of research on influencing factors of entrepreneurial intention but rarely studies the influence mechanism of emotional competences on entrepreneurial intention from the perspective of social entrepreneurship. This article takes college students’ social entrepreneurs as research objects, drawing on Krueger’s model, theory of planned behavior, social cognitive theory, and triadic reciprocal determinism theory. This paper constructs a conceptual model with emotional ability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 53 publications
5
60
1
5
Order By: Relevance
“…In addition, there is a distinct interrelationship and strong correlation between green entrepreneurial self-efficacy and optimism (H2), which is consistent with the results of the literature (Baron, 2010;Tong and Miao, 2019;Chu et al, 2020) There is also a significant interrelationship and correlation between ecological values and a sense of social responsibility (H3). Ecological values and a sense of social responsibility can have a positive mutual promotion effect.…”
Section: Conclusion and Recommendations Conclusionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, there is a distinct interrelationship and strong correlation between green entrepreneurial self-efficacy and optimism (H2), which is consistent with the results of the literature (Baron, 2010;Tong and Miao, 2019;Chu et al, 2020) There is also a significant interrelationship and correlation between ecological values and a sense of social responsibility (H3). Ecological values and a sense of social responsibility can have a positive mutual promotion effect.…”
Section: Conclusion and Recommendations Conclusionsupporting
confidence: 87%
“…Tong and Miao (2019) found that in the learning process of college students, optimism plays a partial mediating role between self-efficacy and academic performance. Chu et al (2020) found that emotional competence has a significant positive impact on entrepreneurial self-efficacy in the process of studying entrepreneurial intentions of Chinese college students, and entrepreneurial self-efficacy plays a mediating role between emotional competence and entrepreneurial intentions. In conclusion, people with higher self-efficacy in green entrepreneurship maintained a more optimistic attitude toward entrepreneurship.…”
Section: Green Entrepreneurial Self-efficacy and Optimismmentioning
confidence: 91%
See 1 more Smart Citation
“…Shahab, Chengang, Arbizu, and Haider (2018) study also showed that selfefficacy affects EI. An evaluation of the relationship between ESE and EI was carried out by Chu, Sun, Yang, Zheng, and Li (2020), and their study found that ESE positively affects EI.…”
Section: Entrepreneurial Self-efficacy and Entrepreneurial Intentionmentioning
confidence: 99%
“…Some studies have outlined that individuals with a high level of entrepreneurial education, entrepreneurial mindset, and creativity are more prone to start their businesses (Hu and Ye, 2017 ; Handayati et al, 2020 ). Additionally, scholars believed that the understanding of entrepreneurial self-efficacy is essential, especially on how to start, manage and develop a new business (Chien-Chi et al, 2020 ; Lingappa et al, 2020 ). Thus, individuals that perceived a high level of self-efficacy will lead to greater cognitive minds.…”
Section: Introductionmentioning
confidence: 99%